Suicide Pattern in Malaysia 2001 - 2005 - Ling, Chin Meei (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2008)
There were a total of 824 suicide cases in Malaysia from the year 2001 -2005. The age group '23 - 35' was noted for the highest suicide frequency (287 cases) followed by '36- 50' (250 cases), 'above 50' (186 cases), '13- 21' (92 cases) and '1 - 12' (nine cases). 76% (624 cases) of824 cases were male while female suicide cases accounted for 24%. There was a distinct pattern in each ethnic group. Indian had the highest suicide rate (12.9 per 100,000 populations). Pesticides poisoning was the most popular methods among the Indians (121 cases) and the natives (30 cases). For the Malay and Chinese, hanging was the most popular method (71 cases). Chinese were noted for the highest frequency of CO poisoning (17 cases), drowning (16 cases), hanging (174 cases), jumped from a height (75 cases), self- immolation (four cases) and 'other' methods (ten cases). The majority (58%) of the suicide cases took place in the domicile of the suicides. Hanging was the most popular method in Perlis (seven cases), Pulau Pinang (133 cases), Terengganu (29 cases) and Kelantan (37 cases). Pesticides poisoning was the most commonly used method in Negeri Sembilan (64 cases), Melaka (40 cases), Pahang (42 cases) and Sarawak (51 cases), Different from the eight states above, the most common suicide method in Kuala Lumpur was jumping from high places (39 cases).